4(12+6w+w)-3=

Simple and best practice solution for 4(12+6w+w)-3= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(12+6w+w)-3= equation:


Simplifying
4(12 + 6w + w) + -3 = 0

Combine like terms: 6w + w = 7w
4(12 + 7w) + -3 = 0
(12 * 4 + 7w * 4) + -3 = 0
(48 + 28w) + -3 = 0

Reorder the terms:
48 + -3 + 28w = 0

Combine like terms: 48 + -3 = 45
45 + 28w = 0

Solving
45 + 28w = 0

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-45' to each side of the equation.
45 + -45 + 28w = 0 + -45

Combine like terms: 45 + -45 = 0
0 + 28w = 0 + -45
28w = 0 + -45

Combine like terms: 0 + -45 = -45
28w = -45

Divide each side by '28'.
w = -1.607142857

Simplifying
w = -1.607142857

See similar equations:

| 7.4-b=6.8 | | 3f=45 | | -15+8x=x | | y-(y+2)=7-(2y+1) | | -7=1-2y | | X^2-39=10 | | 4x^3/3y | | 8×2/3= | | 2(x+5)+2x=50 | | 6=10+2x | | 4=3x+39 | | 2m+6m=102 | | 13t+10=-65 | | X+4(X+6)=1 | | 8-w=-23 | | 0.25p+0-2(10-p)=0 | | 2(x+1)-x-1=1 | | x(5+2x)=532 | | 13t+10=-65whatisT | | 8z-18=2z | | 3x-2(00)=-6 | | 8x+15x-6=40 | | 9x^3+3x^2+3x+1=0 | | 7.75=a-259 | | 4x+7=5x+17-2x | | https://lh5.googleusercontent.com/3z6e-yOwAdr5KjfGYBzzsqpEiae12YjG86rjzwQDvfEsP-fkI94mrrTNu3FV2Kc6pVLGzne5OA=w126 | | 20=4(x+7)-2 | | x=24-3(2x+1) | | 3f-9=14f+1 | | 8y-20=4y | | (x)(2+3x)=320 | | h(n-4)=-3n-4 |

Equations solver categories